Diversidad de aves y su potencial turístico en avistamiento en las riberas del distrito de Belén, Loreto, 2020 - Ruiz Pezo, Jasmin Diomar (2022)
In the Mohenacaño zone there are village with extreme poverty but that has renewable natural resources not taken advantage of what the birdlife, so it is essential to study their resources for his protection and management through tourism, for this reason, it was proposed the objetiv know the birds diversity and his relation with the turistic potential in observation in the riveredge of Belén city, since january to november 2020, by lineal transect and boat census Through of the direct observation and hearing recognition. Its report a richness of 161 species of birds between residents and migratories, compound for 20 órdo and 46 families. The Passeriformes record the major number of families (15) and species (61), followinf by Charadriiformes with 7 families and 21 species, Piciformes with 4 families and 11 species, and Falconiformes and Psittaciformes with one family each one, with 8 and 15 species respectively. The densities they were Brotogeris versicolurus “pihuicho ala blanca” (140.67 ind/km2), Milvago chimachima “shihuango blanco” (96.90 ind/km2) y Chrysomus icterocephala “pájaro amarillo chico” (94.39 ind/km2). The Mohenacaño zone presents basic conditions the infraestructura for the developments the tourism based on observation of birds, but lacks trained staff. Some actions are presented to develop this activity. It is conclude that the diversity of birds reported allows development the tourism in sighting of birdlife riveredge in Mohenacaño zone.